The Boatowner's Guide to GMDSS and Marine Radio : Digital Selective Calling VHF Radio Simulator - Boatowner's... (McGraw Hill, 2006)
Berisi Autorum, CD Instructions, CPSflag, Istall_DSC, LAUNCH, Reg_Em